Eye Donation: Awareness, Knowledge, Willingness, and Barriers among Paramedical and Allied Health Science Students at a Tertiary Care Teaching Hospital in South India - Aimanfatima Kacheri; Rekha Mudhol; Sanjeev Chougule; Rhema Reny; Sagarika Kamath; Rajesh Kamath (The Scientific World Journal)
Background. Visual impairments have physical, emotional, social, and economical consequences and are a crucial element influencing one's quality of life. A total of 1.285 million people are estimated to be visually impaired worldwide of which 39 million are categorised as blind. These figures are startling, given that 80 percent of known vision impairments are either treatable or preventable. Corneal transplants appear to be our best hope for resolving this problem; however, a global shortage of available donors continues to dampen efforts addressing this issue. Methods. This two-year cross-sectional study employed a convenience sampling technique and a standardised questionnaire to survey 150 paramedical and allied health science students at a tertiary care teaching hospital and assessed the awareness, knowledge, willingness and barriers regarding eye donation. Results. The study revealed a 93.3% awareness rate of the donation procedure, of which 46% attributed their awareness to media sources. However, other aspects assessed had much lower awareness rates; when the eyes are donated (53.3%), optimal time period for retrieval of tissue/organ (54%), ideal part transplanted (54%), age limit not restricting donation (67%), donation by donors using spectacles (48%), confidentiality of the donor and recipient (54%), hospital having the facility of an eye bank (63%). 49 percent of the respondents were willing to pledge themselves as eye donors, and a majority of the unwilling respondents reported that familial opposition was the reason for their hesitation. Conclusion. Knowledge levels appear to be below expectations, and more effort is required to ensure that knowledge is imparted to our healthcare practitioners, who will then transfer this knowledge to the population, resulting in an increase in donation rates.